Successful invasion of the Amazon Coast by the giant river prawn, macrobrachium rosenbergii: Evidence of a reproductively viable population - Iketani, Gabriel; Aviz, Manoel Alessandro Borges; Maciel, Cristiana; Valenti, Wagner [UNESP]; Schneider, Horacio; Sampaio, Iracilda (Regional Euro-Asian Biological Invasions Centre Oy (REABIC), 2016)
Macrobrachium rosenbergii has been introduced into a number of countries, and in some of these, it has already been frequently captured in the wild. As for any other exotic species, its success in new habitats is related primarily to its reproductive capacity. For the present study we evaluated the reproductive capacity of an introduced population of M. rosenbergii in estuaries of the Amazon Coast, north Brazil. A total of 588 specimens (305 males and 283 females) were captured during 24 months. Of the females, 82 (28.9%) were incubating eggs, and 62 (21.9%) had recently spawned. In addition, more than 70% of the females had mature or maturing gonads. Mean fecundity was 55,000 eggs, with a minimum of 9,086, and a maximum of 192,172 eggs. Ovigerous females were captured throughout the study period, indicating continuous reproduction. Adult males are known to present three morphotypes, all of which were observed in the present study, but with a predominance of the intermediary Orange Claw morphotype (48%). The body length and weight of males were greater than in females. Different size classes were observed for both sexes during the study period suggesting a continued recruitment of new individuals to the population over the time. The species has been harvested from the wild for more than ten years, being interrupted during the period when the river is flooded. This may function as a natural interval for the recovery of stocks, which may favor the establishment of a sustainable population over the long term. We conclude that the exotic population of M. rosenbergii in eastern Amazonia is capable of reproducing itself and probably has the capacity to persist over future generations, causing a strong impact on native species. Given this, it is important to continue monitoring the progress of this species and its potential effects on the biodiversity of the Amazon basin.
Keywords: Biological invasion; Exotic species; Palaemonidae and Amazonia; Prawn reproduction